2008
DOI: 10.2337/dc07-1313
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Diabetes Self-Management With and Without Automated Telephone Reinforcement

Abstract: OBJECTIVE -To determine 1) whether participants in the Spanish Diabetes SelfManagement Program (SDSMP), when compared at 6 months to randomized control subjects, would demonstrate improvements in health status, health behaviors, and self-efficacy; and 2) whether SDSMP participants receiving monthly automated telephone reinforcement would maintain improvements at 18 months better than those not receiving reinforcement. RESEARCH DESIGN AND METHODS-A total of 567 Spanish-speaking adults with type 2 diabetes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
348
3
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(367 citation statements)
references
References 28 publications
8
348
3
8
Order By: Relevance
“…The strength of the evidence for short-term mortality was graded as moderate, given that results were precise, direct, and had low risk of bias (Table 2). Table 7), 4,21,49,61,62,69,[72][73][74][75][76][77][78][79][80][81][82][83] showing no clear differences between groups in hypoglycemia. The strength of evidence was graded as low, given the inconsistency and imprecision of the results (Table 2).…”
Section: Safetymentioning
confidence: 99%
See 4 more Smart Citations
“…The strength of the evidence for short-term mortality was graded as moderate, given that results were precise, direct, and had low risk of bias (Table 2). Table 7), 4,21,49,61,62,69,[72][73][74][75][76][77][78][79][80][81][82][83] showing no clear differences between groups in hypoglycemia. The strength of evidence was graded as low, given the inconsistency and imprecision of the results (Table 2).…”
Section: Safetymentioning
confidence: 99%
“…Most studies reported hypoglycemia as total hypoglycemic events [75][76][77] (N=5) or p a r t i c i p a n t s e x p e r i e n c i n g h y p o g l y c e m i a ( N = 8). 61,62,69,73,74,78,80,82 Hypoglycemic outcomes were defined heterogeneously, with some studies based on self report 4,21,62,72,73,77,82 and others on glucose readings. 74,76,78 Twelve of the 18 studies reported measures of variability.…”
Section: Safetymentioning
confidence: 99%
See 3 more Smart Citations